Cyanobacterial diversity of western European biological soil crusts along a latitudinal gradient - Williams, Laura (FEMS Microbiol Ecol, 2016)
Cyanobacteria associated with biological soil crusts (BSCs) have important attributes, such as nitrogen fixation and soil stabilisation. However, research on these organisms has been minimal, and their diversity and distribution throughout temperate Europe is currently unknown. The SCIN (Soil Crust International) project is a multidisciplinary research initiative that aims to achieve improved understanding of the BSCs of Europe, one facet being an investigation into the cyanobacterial communities of BSCs across a latitudinal gradient. Cyanobacteria assemblages were analysed by both morphological and molecular analysis. Two treatments were applied prior to DNA extraction, continued sample wetting and a dry sample process, and 16S ribosomal RNA (rRNA) amplicons were processed by Illumina MiSeq sequencing. The results reveal high and variable cyanobacterial diversity with each site showing a unique assemblage. Many common cyanobacterial genera, for example Nostoc and Microcoleus, were found in all sites but the abundances of different genera varied considerably. The polyphasic approach was found to be essential in recording the presence of important cyanobacteria that a single method itself did not highlight. The wet and dry treatments showed some differences in diversity, but mainly in abundance, this may suggest how cyanobacterial composition of BSCs changes with seasonal variability.